Composite psychosocial risk based on the fear avoidance model in patients undergoing anterior cruciate ligament reconstruction: Cluster-based analysis. (July 2021) - Coronado, Rogelio A.; Bley, Jordan A.; Huston, Laura J.; Pennings, Jacquelyn S.; Master, Hiral; Reinke, Emily K.; Bird, Mackenzie L.; Scaramuzza, Erica A.; Haug, Christine M.; Mathis, Shannon L.; Vanston, Susan W.; Cox, Charles L.; et al.
Abstract: Objectives: To examine associations between preoperative fear-avoidance model (FAM) risk subgroup status and patient expectation of surgical success with postoperative outcomes at 6 and 12 months after anterior cruciate ligament reconstruction (ACLR). Design: Cohort study. Setting: Academic medical center. Participants: 54 patients (25 females) undergoing unilateral ACLR. Main outcome measures: Cluster analysis distinguished FAM risk subgroups based on preoperative fear of movement/reinjury, self-efficacy, and pain catastrophizing. Preoperative expectation for surgical success was assessed with a numeric rating scale. Six and 12-month outcomes included Subjective Patient Outcomes for Return to Sport, Knee Injury and Osteoarthritis Outcome Score (KOOS) sports/recreation and quality of life, and International Knee Documentation Committee (IKDC) Subjective Knee Form. Results: Thirteen (24%) patients were "moderate-to-high FAM risk." Moderate-to-high FAM risk patients had lower odds of return to sport at 12 months (OR = 0.3, p = .05) and lower KOOS sports/recreation at 6 months (st. beta = −0.27, p = .05), KOOS quality of life at 12 months (st. beta = −0.42, p = .007), and IKDC at 6 (st. beta = −0.29, p = .04) and 12 months (st. beta = −0.47, p = .001). Higher expectation was associated with lower 6-month IKDC (st. beta = −0.36, p = .008) and 12-month KOOS quality of life (st. beta = −0.29, p = .05). Conclusions: Preoperative FAM risk influences patient-reported outcomes and return to sport at 6 and 12 months. Highlights: 24% of patients were moderate-to-high risk based on fear-avoidance model (FAM) factors. Moderate-to-high FAM risk patients had poorer return to sport and patient-reported outcomes. Expectation of surgical success was an important predictor of 6-month knee function.